Where once was love, love is no more?: What happens to expressions of love in late period Egypt? - Quack, Joachim Friedrich (Die Welt des Orients, 2016)
It has been customary to compare the Biblical Song of Songs with the Egyptian love poetry. However, chronology has always been a problem: The Egyptian texts in question date to the later second millennium BCE (except for the stela Louvre C 100 which takes up some formal elements of love poetry und dates to ca. 700 BCE) while the Biblical composition is normally thought to be from the later first millennium BCE. This contribution will look at possible reasons for this absence of love poetry in late Egypt, but also trace expressions of love in other textual genres during this time. These concern especially lamentations of Osiris sung by Isis and Nephthys (where memories of past love are often evoked), narrative texts (where feelings of love aremuchmore prominent than in older texts), and love charms (which also become much more frequent), but also bawdy songs where sex and orgies are explicitly mentioned.
Gesehen am 23.08.2016